Experimental Study on Humidifier Performance in a Humidification-Dehumidification System. Issue 1 (1st February 2022) - Ge, Hongyu; Cai, Yisong; Kang, Peisen; Liu, Jiawei; Liu, Xiaohua
Abstract: The characteristic of Humidification-dehumidification seawater desalination technology is flexible scale. It is suitable for dispersive fresh water demand and easy to couple with low-grade energy. In this study, an experimental platform of humidifier performance is designed to investigate the influence of spray flow, spray liquid temperature, air flow, hole diameter, pitch of holes and the number of sieve plates on moisture content of humid air at outlet and evaporation capacity. The results show that, when the spray flow and temperature increase, the moisture content of outlet air and evaporation capacity increase. The evaporation capacity increases when the extent of the air flow increasing is more than that of the moisture content decreasing. When the spray flow is 0.025kg/s, the evaporation capacity is the highest when the sieve plate with the hole diameter of 3.0mm and the holes pitch of 9.0mm is used. For other flow conditions, the evaporation rate is the highest when the sieve plate with the hole diameter of 2.5mm and the hole pitch of 7.5mm is used. The evaporation capacity with double sieve plates is higher than that with single sieve plate. The research of this paper provides guidance for practical application of the HDH seawater desalination system.